Bilayered chitosan-based scaffolds for osteochondral tissue engineering : influence of hydroxyapatite on in vitro cytotoxicity and dynamic bioactivity studies in a specific double-chamber bioreactor - Malafaya, P. B. (2009)
Osteochondral tissue engineering presents a current research challenge due to the necessity of combining both bone and cartilage tissue engineering principles. In the present study, bilayered chitosan-based scaffolds are developed based on the optimization of both polymeric and composite scaffolds. A particle aggregation methodology is proposed in order to achieve an improved integrative bone–cartilage interface needed for this application, since any discontinuity is likely to cause long-term device failure. Cytotoxicity was evaluated by the MTS assay with the L929 fibroblast cell line for different conditions. Surprisingly, in composite scaffolds using unsintered hydroxyapatite, cytotoxicity was observed in vitro. This work reports the investigation that was conducted to overcome and explain this behaviour. It is suggest that the uptake of divalent cations may induce the cytotoxic behaviour. Sintered hydroxyapatite was consequently used and showed no cytotoxicity when compared to the controls. Microcomputed tomography (micro-CT) was carried out to accurately quantify porosity, interconnectivity, ceramic content, particle and pore sizes. The results showed that the developed scaffolds are highly interconnected and present the ideal pore size range to be morphometrically suitable for the proposed applications. Dynamical mechanical analysis (DMA) demonstrated that the scaffolds are mechanically stable in the wet state even under dynamic compression. The obtained elastic modulus was, respectively, 4.21 ± 1.04, 7.98 ± 1.77 and 6.26 ± 1.04 MPa at 1 Hz frequency for polymeric, composite and bilayered scaffolds. Bioactivity studies using both a simulated body fluid (SBF) and a simulated synovial fluid (SSF) were conducted in order to assure that the polymeric component for chondrogenic part would not mineralize, as confirmed by scanning electron microscopy (SEM), inductively coupled plasma-optical emission spectroscopy (ICP) and energy-dispersive spectroscopy (EDS) for different immersion periods. The assays were carried out also under dynamic conditions using, for this purpose, a specifically designed double-chamber bioreactor, aiming at a future osteochondral application. It was concluded that chitosan-based bilayered scaffolds produced by particle aggregation overcome any risk of delamination of both polymeric and composite parts designed, respectively, for chondrogenic and osteogenic components that are mechanically stable. Moreover, the proposed bilayered scaffolds could serve as alternative, biocompatible and safe biodegradable scaffolds for osteochondral tissue engineering applications.